PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Made Dewi Antari; I Wayan Widnyana; I Gusti Ngurah Bagus Gunadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
The purpose of this study is to examine the effect of the implementation of Good Corporate Governance on the financial performance of banks. Financial performance is measured by return on equity (ROE). The type of research used is the type of quantitative and qualitative research. This study uses secondary data obtained from the annual reports of banking companies listed on the Indonesia Stock Exchange (IDX). The data were analyzed using multiple regression analysis with the help of SPSS version 25 program. The results of this study indicate (1) the Board of Commissioners has no effect on the Financial Performance of the Bank. (2) The Board of Directors has a positive and significant effect on the Financial Performance of the Bank. (4) Institutional Ownership has an effect on negative on the Financial Performance of the Bank. (5) Managerial Ownership has no effect on the financial performance.